Origin of blocky aragonite cement in Cenozoic glaciomarine sediments, McMurdo Sound, Antarctica. Issue 2 (26th December 2019) - Yang, Mingyu; Frank, Tracy D.; Fielding, Christopher R.; Smith, Megan E.; Swart, Peter K.
Abstract: Inorganic aragonite occurs in a wide spectrum of depositional environments and its precipitation is controlled by complex physio‐chemical factors. This study investigates diagenetic conditions that led to aragonite cement precipitation in Cenozoic glaciomarine deposits of McMurdo Sound, Antarctica. A total of 42 sandstones that host intergranular cement were collected from the CIROS‐1 core, located proximal to the terminus of Ferrar Glacier. Standard petrography, Raman spectroscopy and electron microprobe analysis reveal a prominent aragonite cement phase that occurs as a pore‐filling blocky fabric throughout the core. Oxygen isotope compositions ( δ 18 O = −30·0 to −8·6‰ Vienna Pee‐Dee Belemnite) and clumped isotope temperatures (TΔ47  = 13·1 to 31·5°C) determined from the aragonite cements provide precise constraints on isotopic compositions ( δ 18 Ow ) of the parent fluid, which mostly range from −10·8 to −7·2‰ Vienna Standard Mean Ocean Water. The fluid δ 18 Ow values are consistent with those of pore water, previously identified as cryogenic brine in the nearby AND‐2A core. Petrographic and geochemical data suggest that aragonite cement in the CIROS‐1 core precipitated from a similar brine. The brine likely formed and infiltrated sediments in flooded glacial valleys along the western margin of McMurdo Sound during the middle Miocene Climatic Transition, and subsequently flowed basinward in the subsurface. Consequently, the brine forms as a longstanding subsurface fluid that has saturated Cenozoic sediments below southern McMurdo Sound since at least the middle Miocene. Aragonite cementation in the CIROS‐1 core is interpreted to reflect its proximal position to sites of brine formation and greater likelihood of experiencing brines with sustained high carbonate saturation states and Mg/Ca ratios. This unusual occurrence expands the range of known natural occurrences of aragonite cement. Given the potential for cryogenic brine formation in glaciomarine settings, blocky aragonite, as the end member of the spectrum of aragonite cement morphology, may be more widespread in glaciomarine sediments than currently thought.